1996
DOI: 10.1002/cbf.639
|View full text |Cite
|
Sign up to set email alerts
|

Inositolphosphoglycans and diacylglycerol are possible mediators in the glycogenic effect of GLP‐1(7‐36)amide in BC3H‐1 myocytes

Abstract: A potent glycogenic effect of GLP-1(7-36)amide has been found in rat hepatocytes and skeletal muscle, and specific receptors for this peptide, which do not seem to be associated with the adenylate cyclase-cAMP system, have been detected in these tissue membranes. On the other hand, inositolphosphoglycan molecules (IPGs) have been implicated as second messengers of the action of insulin. In this work, we have found, in differentiated BC3H-1 myocytes, specific binding of [125I]GLP-1(7-36)amide, and a stimulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…In these tissues, GLP-1 does not stimulate cAMP but induces the rapid hydrolysis of GPIs (Márquez et al, 1998;Luque et al, 2002) related to a short-lived generation of IPGs , a well characterized signaling pathway in the action of different hormones (Jarett and Seals, 1979;Larner et al, 1979;Suzuki et al, 1984a,b;Larner, 1988). In the present study, GLP-1 has shown to promote the immediate hydrolysis of GPIs in osteoblastic MC3T3-E1 cellsmaximal between 1 and 2 min-and its subsequent re-synthesis thereafter, following the same pattern than that previously shown in other extrapancreatic tissues and cells (Galera et al, 1996;Márquez et al, 1998;Luque et al, 2002). These data suggest that IPGs could be acting as second messengers of the GLP-1 receptor in osteoblastic cells.…”
Section: Discussionsupporting
confidence: 87%
“…In these tissues, GLP-1 does not stimulate cAMP but induces the rapid hydrolysis of GPIs (Márquez et al, 1998;Luque et al, 2002) related to a short-lived generation of IPGs , a well characterized signaling pathway in the action of different hormones (Jarett and Seals, 1979;Larner et al, 1979;Suzuki et al, 1984a,b;Larner, 1988). In the present study, GLP-1 has shown to promote the immediate hydrolysis of GPIs in osteoblastic MC3T3-E1 cellsmaximal between 1 and 2 min-and its subsequent re-synthesis thereafter, following the same pattern than that previously shown in other extrapancreatic tissues and cells (Galera et al, 1996;Márquez et al, 1998;Luque et al, 2002). These data suggest that IPGs could be acting as second messengers of the GLP-1 receptor in osteoblastic cells.…”
Section: Discussionsupporting
confidence: 87%
“…However, several studies have shown that in the liver and skeletal muscle, GLP-1 seems to act through specific receptors, different in structure and signaling pathways from those in the pancreas, which are cAMP associated. Second messengers such as inositol phosphoglycan or phosphatidylinositol 3-phosphate have been proposed (18,23,28,40). In a more recent study (1), activation of phosphatidylinositol 3Ј-kinase, protein kinase B, and mitogen-activated protein kinases has been shown to be involved in the action of GLP-1 upon glycogen synthase a activity in rat skeletal muscle.…”
Section: Discussionmentioning
confidence: 97%
“…Further, two groups have reported that GLP-1 has insulin-like activity and stimulates glycogen formation (59) and inhibits glycogenolysis (27) in isolated hepatocytes. These investigators suggest that GLP-1 action in the liver is mediated by receptors that are different in structure and signaling pathways (20,26,27,32,38,56,59). It is also possible that Ex-4 is mediating its actions in the IUGR neonate through GLP-1 receptors in the portal vein, as a number of investigators have shown that Ex-4 can reduce glucose, independent of islet hormones or gastric emptying (3,4,9,28,38,39,41,57).…”
Section: Discussionmentioning
confidence: 99%